Recognition and management of clinically significant drug–drug interactions between antiretrovirals and co-medications in a cohort of people living with HIV in rural Tanzania: a prospective questionnaire-based study. (2nd August 2021) - Kuemmerle, Andrea; Sikalengo, George; Vanobberghen, Fiona; Ndege, Robert C; Foe, Gideon; Schlaeppi, Chloé; Burri, Christian; Battegay, Manuel; Paris, Daniel H; Glass, Tracy R; Weisser, Maja; Marzolini, Catia; et al.
Abstract: Background: The extent to which drug–drug interactions (DDIs) between antiretrovirals (ARVs) and co-medications are recognized and managed has not been thoroughly evaluated in limited-resource settings. Objectives: This prospective questionnaire-based study aimed to determine the prevalence and risk factors for unrecognized/incorrectly managed DDIs in people living with HIV followed-up at the Chronic Diseases Clinic of Ifakara (CDCI) and enrolled in the Kilombero and Ulanga Antiretroviral Cohort (KIULARCO). Methods: We prospectively included ARV-treated adults receiving ≥1 co-medication coming for a follow-up visit at the CDCI between March and July 2017. Using a structured questionnaire, physicians were requested to identify potentially clinically significant DDIs in the prescribed treatment, to provide recommendations for their management and to indicate any hurdles to implement the recommendations. Prescriptions were subsequently screened for DDIs using the Liverpool DDIs database. Identified clinically significant DDIs and their recommended management according to the DDIs database were compared with the information provided in the questionnaires. Results: Among 334 participants, the median age was 47 years (IQR = 40–56 years), 69% were female and 82% had ≥1 non-communicable disease (NCD). Overall, 129 participants had ≥1 clinically relevant DDI, which was not recognized and/or incorrectly managed in 56 participants (43%). Of those, 6 (11%) were due to limited monitoring options or medication affordability issues. In the multivariable logistic regression, the presence of ≥1 NCD was associated with an increased risk for unrecognized/incorrect DDI management (OR = 15.8; 95% CI = 1.8–139.6). Conclusions: Recognition/appropriate management of DDIs is suboptimal, highlighting the need for educational programmes, pharmacovigilance activities and increased access to medications and monitoring options. This should become a focus of HIV programmes given the increasing burden of NCDs in sub-Saharan Africa.